2008
DOI: 10.1002/pc.20711
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of oxygen barrier properties of organoclay/HDPE/EVA nanocomposite films prepared using a two‐step solution method

Abstract: In this article, oxygen barrier properties of nanocomposite films composed of organoclay (OC), high‐density polyethylene (HDPE), and ethylene vinyl acetate (EVA) copolymer have been investigated. The nanocomposite films whose EVA forms a dominant fraction were prepared using the solution method. The dispersion of the OC in the HDPE/EVA blend was improved through taking two‐step procedure in the preparation of nanocomposite. First, the OC and EVA were dissolved in chloroform. Then, the resulting product, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…A weight loss was registered in all cases in the range of 250-510 °C. A similar weight loss pattern was reported by Abdul et al [30] and Reza et al [31] for high density pe.…”
Section: Resultssupporting
confidence: 89%
“…A weight loss was registered in all cases in the range of 250-510 °C. A similar weight loss pattern was reported by Abdul et al [30] and Reza et al [31] for high density pe.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, combining it with another material, such as polypropylene, its gas/steam resistance can be improved (Dadfar et al . ). The deterioration by dehydration in the food product is a quality variable that must be considered in dry environments.…”
Section: Resultsmentioning
confidence: 97%
“…HDPE represents a powerful barrier against moisture, useful to the food packaging industry; however, this material is a poor barrier against oxygen. Therefore, combining it with another material, such as polypropylene, its gas/steam resistance can be improved (Dadfar et al 2009). The deterioration by dehydration in the food product is a quality variable that must be considered in dry environments.…”
Section: Water Activity Kineticsmentioning
confidence: 99%
“…35 Dadfar et al have also reported the increase in oxygen permeability with increasing EVA concentration in HDPE/EVA/MMT system. 36 …”
Section: Oxygen Barrier Propertiesmentioning
confidence: 99%